2021
DOI: 10.3389/fcell.2020.614624
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive and Multiplexed Protein Imaging With Cleavable Fluorescent Tyramide Reveals Human Neuronal Heterogeneity

Abstract: The ability to comprehensively profile proteins in intact tissues in situ is crucial for our understanding of health and disease. However, the existing methods suffer from low sensitivity and limited sample throughput. To address these issues, here we present a highly sensitive and multiplexed in situ protein analysis approach using cleavable fluorescent tyramide and off-the-shelf antibodies. Compared with the current methods, this approach enhances the detection sensitivity and reduces the imaging time by 1–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 73 publications
2
14
0
Order By: Relevance
“…To enable highly sensitive and multiplexed protein imaging with off-the-shelf antibodies, our group developed a reiterative protein staining approach using cleavable fluorescent tyramide (CFT) [17]. We demonstrated that its sensitivity is improved by about two orders of magnitude compared with other existing methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To enable highly sensitive and multiplexed protein imaging with off-the-shelf antibodies, our group developed a reiterative protein staining approach using cleavable fluorescent tyramide (CFT) [17]. We demonstrated that its sensitivity is improved by about two orders of magnitude compared with other existing methods.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, with tris(2-carboxyethyl) phosphine (TCEP) as the signal removal reagent, the first-generation CFT requires 65 • C to remove~95% of the staining signals. Therefore, this relatively high reaction temperature could damage the integrity of the epitopes [17].…”
Section: Introductionmentioning
confidence: 99%
“…Without signal amplification, the low detection sensitivity of these methods limits their applications to study low-expression proteins or to examine specimens with high autofluorescence, such as formalin-fixed paraffin-embedded (FFPE) tissues [18]. To tackle these issues, several laboratories, including ours, have developed several sensitive and multiplexed protein imaging technologies by signal amplifications with biotin-streptavidin interaction [19], oligonucleotide hybridization [20], and horseradish peroxidase (HRP) [21,22]. However, these methods require a chemical-, oligonucleotide-or HRP-labeled primary antibodies to recognize the protein targets.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the fluorophore cleavage efficiency, we stained mRNA PPIB in an FFPE mouse lung tissue using tyramide-N 3 -Cy5 ( Figure 1 D). This CFT molecule has been recently developed in our laboratory for multiplexed protein imaging [ 27 ]. We have demonstrated that tyramide-N 3 -Cy5 can be successfully converted by HRP to a short-lived reactive radical.…”
Section: Resultsmentioning
confidence: 99%
“…Integrated in situ analysis of RNA and proteins in the same specimen is of increasing importance in studies of gene expression regulation [ 29 ] and disease diagnosis [ 30 ]. Our laboratory recently developed cleavable fluorescent probes [ 27 , 31 , 32 , 33 ] for multiplexed protein imaging and demonstrated that these probes enable a large amount of different proteins to be accurately quantified in their native cellular contexts in single cells. To evaluate whether the multiplexed RNA and proteins in situ analysis can be combined in the same tissue using CFT, we stained two proteins and five mRNA sequentially using tyramide-N 3 -Cy5 in a mouse spinal cord tissue ( Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%